Print Rights with a Thousand Masks: Migrant Vulnerability, Resistance and Human Rights Law - Dez, Jordan F. (Refuge: Canada's Journal on Refugees, 2022)
PrintRights, a cooperative of undocumented asylum-seekers in Amsterdam, manufactured facemasks during the Covid-19 pandemic; first distributing them to undocumented migrants residing in the city’s emergency shelter system and then selling them on-line to the wider public. By distributing facemasks with a message, PrintRights performatively inhabited the right to distribute printed works, legally resisting alienage law prohibitions on employment. Engaging the theory of Judith Butler, this article analyzes the relationship between PrintRights’ resistance, vulnerability and human rights discourse. Drawing on fieldwork conducted with PrintRights, this article shows the potential of human rights discourse to support undocumented migrant resistance.